IBM PEMBERDAYAAN KAUM PEREMPUAN MELALUI INOVASI PENGOLAHAN MIE RUMPUT LAUT - Mailoa, Meigy Nelce; Gaspersz, Febe F; Setha, Beni (Balobe: Jurnal Pengabdian Masyarakat, 2022)
Wael and Kotania villages are one of the centers for seaweed production in the Kotania Bay waters in the West Seram Regency. Most of the women in Wael and Kotania hamlets, especially mothers, do not have permanent jobs other than taking care of the household. In addition, there is a lack of knowledge in seaweed processing technology. To empower women in the hamlets of Wael and Kotania, it is necessary to create productive activities by utilizing the potential of the village, both the potential of human resources and natural resources. The solution offered to women in the hamlets of Wael and Kotania through this IbM activity is the establishment of a business through the innovation of processing Eucheuma cottonii seaweed into noodles. Activity Objectives 1) Improving women's knowledge and skills about seaweed noodle processing technology. 2) Improving women's knowledge and skills about financial management and marketing strategies for seaweed noodle products. 3) Creating alternative livelihoods for women in coastal areas. Benefits of Activities 1) Empowering women in an effort to increase family income. 2) Realizing the tridharma of higher education through community service. 3) Build a seaweed noodle processing industry in rural areas on a home industrial scale. The addition of seaweed in the manufacture of noodles is expected to increase the consumption of more varied nutrition for the wider community and fulfill nutritional needs, especially micronutrients, one of which is iodine. Processing of seaweed into processed food products by women is expected to increase family income